Pengaruh Pengendalian Internal terhadap Tingkat Korupsi (Studi Empiris pada Pemerintah Provinsi di Indonesia tahun 2021-2023) - Tito Mahmudi; Nadhir Faisal; Laurenza Sitorus; Gevin Kurniawan; Camiliya Faza Aulia (Universitas Budi Luhur, 2025)
This study aims to analyze the influence of the effectiveness of internal control systems on the level of corruption in provincial governments in Indonesia during the 2022–2024 period. Internal control is measured using the maturity level of the Government Internal Control System (SPIP) published by BPKP, while the level of corruption is proxied by the actual number of corruption cases reported by Indonesia Corruption Watch. Using a quantitative approach with a Random Effect panel data regression model, the analysis reveals that the maturity level of SPIP has no significant effect on variations in corruption levels. This finding suggests that SPIP implementation in most provincial governments remains largely administrative and has not been fully internalized into the organizational culture. The study highlights the need to strengthen SPIP effectiveness through enhanced supervisory capacity and the integration of ethical and integrity values into public governance practices.